2003
DOI: 10.1161/01.str.0000068409.81859.c5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Linear Dynamics of Cerebrovascular System After Severe Traumatic Brain Injury

Abstract: Background and Purpose-We sought to describe the dynamic changes in the cerebrovascular system after traumatic brain injury by transfer function estimation and coherence. Methods-In 42 healthy volunteers (meanϮSD age, 37Ϯ17 years; range, 17 to 65 years), spontaneous fluctuations of middle cerebral artery blood flow velocity and of finger blood pressure (BP) were simultaneously recorded over a period of 10 minutes under normocapnic and hypocapnic conditions to generate normative spectra of coherence, phase shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…As dynamic CA becomes less efficient, the return of CBFV slows and often does not reach the original baseline level. Clinical conditions where CA could be expected to be impaired, such as carotid artery disease (14,35), subarachnoid hemorrhage (18), severe head injury (22,33), ischemic stroke (17), MCA stenosis (13), autonomic failure (3,42), malignant hypertension (16), and neonatal prematurity (25,39), support the predicted changes in coherence, gain, phase, and CBFV step responses described above. Similar behavior was also observed during hypercapnia, which is known to reduce the efficiency of static and dynamic CA (1,11,26,34).…”
Section: Discussionsupporting
confidence: 54%
“…As dynamic CA becomes less efficient, the return of CBFV slows and often does not reach the original baseline level. Clinical conditions where CA could be expected to be impaired, such as carotid artery disease (14,35), subarachnoid hemorrhage (18), severe head injury (22,33), ischemic stroke (17), MCA stenosis (13), autonomic failure (3,42), malignant hypertension (16), and neonatal prematurity (25,39), support the predicted changes in coherence, gain, phase, and CBFV step responses described above. Similar behavior was also observed during hypercapnia, which is known to reduce the efficiency of static and dynamic CA (1,11,26,34).…”
Section: Discussionsupporting
confidence: 54%
“…Two previous studies have suggested that there are nonlinear factors in cerebral hemodynamic. 4,5 In the first article, 4 nonlinearity was assumed attributable to poor fit of linear models to the observed data. In the second article, 5 the nonlinear behavior was inferred from the shape of the coherence, phase, and amplitude characteristics.…”
mentioning
confidence: 99%
“…To calculate the coherence between left and the right, the coherence value was estimated by [24, 25]T1Cxyf=Pxyf2PxxfPyyf,where P xy ( f ) = ∫ − ∞ ∞ R xy ( t ) e − jft dt ; thus P xy ( f ) is the Fourier transform of the R xy ( R xy is the cross-correlation of x and y ). Equation (2) obtains the magnitude squared coherence estimate C xy ( f ) of the input signals x and y using Welch's averaged, modified periodogram method.…”
Section: Methodsmentioning
confidence: 99%